1981
DOI: 10.1001/archderm.117.8.500
|View full text |Cite
|
Sign up to set email alerts
|

Premalignant lymphoid hyperplasia preceding and coexisting with malignant lymphoma in the skin

Abstract: A primary malignant lymphoma of the skin had concurrent and antecedent lesions showing histologic changes of completely benign lymphoid hyperplasia. The malignant lymphoma itself evolved during a few years, although specimens from repeated biopsies had previously exhibited benign lymphoid hyperplasia. We urge that persistent benign lymphoid hyperplasia in its many clinical forms in the skin be recognized as a long-term premalignant lesion. Awareness of such a continuum of benign to malignant change aids in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…To our knowledge, no previous studies of vulvar lymphoma arising in the setting of lymphoma‐like lesion have been reported. In non‐vulvar skin, some cases of cutaneous pseudolymphoma evolving into cutaneous lymphoma have been described 25–29 ; in fact, marginal zone lymphoma arises in a background of lymphoid hyperplasia induced by various antigenic stimuli, including EBV and B. burgdorferi infection 30 . In the present case, we were not able to demonstrate infection of EBV nor B. burgdorferi by PCR methods.…”
Section: Discussioncontrasting
confidence: 59%
“…To our knowledge, no previous studies of vulvar lymphoma arising in the setting of lymphoma‐like lesion have been reported. In non‐vulvar skin, some cases of cutaneous pseudolymphoma evolving into cutaneous lymphoma have been described 25–29 ; in fact, marginal zone lymphoma arises in a background of lymphoid hyperplasia induced by various antigenic stimuli, including EBV and B. burgdorferi infection 30 . In the present case, we were not able to demonstrate infection of EBV nor B. burgdorferi by PCR methods.…”
Section: Discussioncontrasting
confidence: 59%
“…This ‘continuous spectrum of B‐cell neoplasia’ has also been described in other extranodal lymphoid hyperplasias 51 . Cases of pseudolymphoma ‘evolving’ into cutaneous lymphoma have been described 27, 28 , 52–55 . A monoclonal population in CLH, detected by molecular methods, is considered grounds for a systemic disease work‐up and regular follow‐up 7, 29 , 52 .…”
Section: Discussionmentioning
confidence: 85%
“…The lymphoma incidence rate of Myc/latency mice was marginally higher than that of the single KSHV transgenic mice, which was 17.1%, but significantly higher than in the Myc mice (4.8%, p ≤ 0.016 by F-test). Lymphoid hyperplasia can progress to frank lymphoma [ 36 38 ]. The combined rate for incidence of lymphoma and lymphoid hyperplasia was higher in Myc/latency mice (77.5%) than latency (69.1%) or Myc mice (43.9%).…”
Section: Resultsmentioning
confidence: 99%